1999
DOI: 10.1086/314825
|View full text |Cite
|
Sign up to set email alerts
|

TT Virus Infection in Patients with Hepatitis C: Frequency, Persistence, and Sequence Heterogeneity

Abstract: TT virus (TTV) was recently identified in the serum of a patient with hepatitis. The role of TTV in liver disease has not been established. Three polymerase chain reaction (PCR) protocols were used to detect TTV DNA in sera of persons infected with hepatitis C virus (HCV) and in blood donors. Sera from 11.5% of HCV-infected patients and 7.7% of blood donors were positive by protocols 1 or 2. In contrast, 48.7% and 57.7% of sera, respectively, were positive when tested by protocol 3. There was no difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
31
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
6
31
1
Order By: Relevance
“…These isolates differed by less than 2% in the remainder of their nucleotide sequences. An alignment of these isolates with 79 previously reported TT virus genotypes permits the proposal of TT virus genera and species within the family Anelloviridae in analogy to a previous proposal for the papillomaviruses (family Papillomaviridae).TT viruses (TTV) are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals where they persist over time (14,16,27,41). Viral particles have been purified from feces (17, 34) and, in addition, are excreted in saliva, breast milk, and bile juice (9,38,47,49).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…These isolates differed by less than 2% in the remainder of their nucleotide sequences. An alignment of these isolates with 79 previously reported TT virus genotypes permits the proposal of TT virus genera and species within the family Anelloviridae in analogy to a previous proposal for the papillomaviruses (family Papillomaviridae).TT viruses (TTV) are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals where they persist over time (14,16,27,41). Viral particles have been purified from feces (17, 34) and, in addition, are excreted in saliva, breast milk, and bile juice (9,38,47,49).…”
mentioning
confidence: 75%
“…TT viruses (TTV) are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals where they persist over time (14,16,27,41). Viral particles have been purified from feces (17, 34) and, in addition, are excreted in saliva, breast milk, and bile juice (9,38,47,49).…”
mentioning
confidence: 99%
“…Several reports have indicated that TTV is associated with a persistent infection (Nishizawa et al, 1997 ;Simmonds et al, 1998 ;Irving et al, 1999). However, there has been no information regarding the stability of TTV DNA titres during persistent infection.…”
Section: Ttv Populations Within Individualsmentioning
confidence: 99%
“…One possible factor involved in generating such genetic diversity is virus persistence. TTV DNA has been detected in samples obtained from hepatitis C virus co-infected individuals for periods of up to 6 years (Irving et al, 1999), and in a cohort of Scottish haemophiliacs many years after the receipt of the likely contaminated batch of clotting factors .…”
Section: Introductionmentioning
confidence: 99%
“…They display over 30% nucleotide diversity (19) and are classified into five distantly related groups (13). TTVs are ubiquitous in nature and have been demonstrated in more than 90% of serum samples from healthy individuals, where they persist over time (5,10,12,16). A tissue culture system that supports efficient replication of TTV is not yet available (4, 13), and this has delayed the study of both TTV genome replication and TTV gene expression.…”
mentioning
confidence: 99%